Transcriptional regulation of metal metabolism- and nutrient absorption-related genes in Eucalyptus grandis by arbuscular mycorrhizal fungi at different zinc concentrations - Xinyang Wang; Jingwei Liang; Ziyi Liu; Yuxuan Kuang; Lina Han; Hui Chen; Xianan Xie; Wentao Hu; Ming Tang (BMC Plant Biology, 2022)
Abstract Background Eucalyptus spp. are candidates for phytoremediation in heavy metal (HM)-polluted soils as they can adapt to harsh environments, grow rapidly, and have good economic value. Arbuscular mycorrhizal fungi (AMF) are the most widely distributed plant symbiotic fungi in nature, and they play an important role in promoting the phytoremediation of HM-polluted soils. However, few studies have evaluated the HM detoxification mechanism of E. spp. in symbiosis with AMF, and thus, the molecular mechanism remains unclear. Results The gene transcription and metabolic pathways of E. grandis were studied with and without inoculation with AMF and at different zinc (Zn) concentrations. Here, we focused on the transcript level of six HM-related gene families (ZNT, COPT/Ctr, YSL, ZIFL and CE). Under high-Zn conditions, thirteen genes (ZNT:2, COPT/Ctr:5, YSL:3, ZIFL:1, CE:2) were upregulated, whereas ten genes (ZNT:3, COPT/Ctr:2, YSL:3, ZIFL:1, CE:1) were downregulated. With AMF symbiosis under high-Zn conditions, ten genes (ZNT:4, COPT/Ctr:2, YSL:3, CE:1) were upregulated, whereas nineteen genes (ZNT:9, COPT/Ctr:2, YSL:3, ZIFL:4, CE:1) were downregulated. Under high-Zn conditions, genes of three potassium-related transporters, six phosphate transporters (PHTs), and two nitrate transporters (NRTs) were upregulated, whereas genes of four potassium-related transporters,four PHTs, and four nitrogen-related transporters were downregulated. With AMF symbiosis under high-Zn conditions, genes of two potassium-related transporters, six ammonium transporters (AMTs) and five PHTs were upregulated, whereas genes of six potassium-related transporters, two AMTs and five PHTs were downregulated. Conclusions Our results indicates that AMF increases the resistance of E. grandis to high-Zn stress by improving nutrients uptake and regulating Zn uptake at the gene transcription level. Meanwhile, our findings provide a genome-level resource for the functional assignments of key genes regulated by Zn treatment and AM symbiosis in six HM-associated gene families and macromineral nutrient-related gene families of E. grandis. This may contribute to the elucidation of the molecular mechanisms of the response to Zn stress in E. grandis with AM symbiosis at the aspect of the interaction between HM tolerance and nutrient acquisition.